(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper we are going to implement distributed framework for performing a simple computation, on mobile computing devices. A central server should take a large computation and decompose it. Mobile computing devices will then be allowed to connect to the server. Connecting, the devices will assign tasks to complete, and upon completing the tasks, the results will be sent back to the server to be mapped. The inherent problems of mobile computing such as resource scarcity, security and low connectivity pose problems for most applications. However, the dynamic nature of mobile computing makes sharing and coordinating work difficult. We help by pooling together the processing power of mobile devices within a crowd to form mobile cloud. We explore this concept of ‘work stealing’ crowd computing in a distributed processing on an opportunistic network and focus on the optimized processing of work. Current work stealing mechanism, security can be specified wherein the data transmitted across the crowd network will be secured using encryption techniques and the system Algorithm is generated which states the techniques and working.